Impact of Re-Warm-Up During Resistance Training: Analysis of Mechanical and Physiological Variables - Pedro P. Neves; Diogo L. Marques; Henrique P. Neiva; Daniel A. Marinho; Ricardo Ferraz; Mário C. Marques; Ana R. Alves (Sports)
Objectives: This study examined the effects of re-warm-up versus no re-warm-up before squats or bench presses on mechanical, physiological, and psychophysiological responses in recreationally trained men. Methods: Twenty-two participants (22.8 ± 3.3 years) completed four randomized sessions involving different re-warm-up and exercise sequences. Measurements included heart rate, blood lactate, tympanic temperature, and perceived exertion. Key performance metrics, such as mean propulsive velocity, peak velocity, power, velocity loss, and effort index, were analyzed. Results: Findings revealed that re-warming up before squats (W + BP + RW + SQ) significantly enhanced propulsive velocity and power compared to no re-warm-up (W + BP + SQ) (p ≤ 0.05; d = 0.45–0.62). However, re-warming up before the bench press (W + SQ + RW + BP) did not improve mechanical performance compared to the standard sequence (W + SQ + BP) (p > 0.05; d = 0.10–0.38). Notably, velocity loss and effort index were higher in the third bench press set under the W + SQ + BP condition (p ≤ 0.05; d = 0.53–0.60). No significant differences in physiological or psychophysiological responses were found between conditions. Conclusions: Overall, re-warm-up effectively improved squat mechanical performance when performed after the bench press but had a minimal impact on the bench press when performed after squats. These findings suggest that re-warming up before lower-body exercises may enhance mechanical performance, while its benefits may be less pronounced for upper-body exercises.